Three-dimensional (3D) reconstruction of structures and landscapes: A new point-and-line fusion method. (October 2019) - Zhou, Ying; Wang, Lingling; Love, Peter E.D.; Ding, Lieyun; Zhou, Cheng
Abstract: The technique of three-dimensional (3D) reconstruction is widely used to develop infrastructure and landscape models to manage cities and assets better. Accurately reconstructing 3D structures (e.g., planes or lines) is a core step in rebuilding a model, especially within a built environment, where piece-wise planar/linear structures predominately prevail. As high-resolution images of large areas have become increasingly accessible, this paper develops an improved 3D reconstruction pipeline using the combination of point and line features. By introducing a dense reconstruction algorithm, which is an improved patch based stereo matching algorithm, this paper presents a robust approach that can be used to overcome the inaccuracies, integrity and reconstruction inefficiencies associated with point clouds. A 3D line extraction method is added to reconstruct accurate edges of buildings. The experimental results demonstrate that the proposed method visually improves the reconstruction effect of a 3D structure and a model's visualization.